PUBG ban and issues of online child safety during COVID-19 lockdown in India: A critical review from the Indian information technology act perspectives - Halder Debarati (Temida)
In June 2020 India opted for banning 59 Chinese Apps. Contrary to the apprehension of banning gaming apps including PUBG, the government did not do so when the Chinese apps were banned. But soon PUBG also got banned in India. Several stakeholders had raised their concerns in this regard as PUBG may affect the mental health of children who are the major users of this app. But on the other hand, it had been observed that PUBG had remained the biggest respite for children who were confined to homes due to COVID- 19. S.69A of the Information Technology Act 2000 (amended in 2008) had been the main tool by the government to block access to Chinese apps. PUBG developers had however tried to outsmart S.69A of the Information Technology Act, 2000 (amended in 2008), which had been used primarily to block the website and by using Artificial Intelligence for preventing children below 18 from being engaged for a continuous period, being exposed to nudity, etc. This article aims to analyse the tussle between the scope and inherent meaning of S.69A and 79 of the Indian Information technology Act, 2000 (amended in 2008) and the ever-developing due diligence of the game developers with special concern for child safety and mental health of the children, which may make the later a winner or a loser in the legal battleground.